2021
DOI: 10.1093/infdis/jiab375
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Response and Serological Estimation of Time Since Infection

Abstract: Background Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) induces a complex antibody response that varies by orders of magnitude between individuals and over time. Methods We developed a multiplex serological test for measuring antibodies to five SARS-CoV-2 antigens and the Spike proteins of seasonal coronaviruses. We measured antibody responses in cohorts of hospitalized patients and healthcare w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…In our 8-month follow-up, we also reported that 76% of the patients still had detectable Neutralizing Antibodies (NAb) (1). Many studies reported short-term follow-up observations of less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others reported longitudinal observations, typically spanning less than 12 months post symptom onset (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Some studies reported contraction of anti-COVID humoral responses with a stronger initial decline (1,4,(23)(24)(25)27).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In our 8-month follow-up, we also reported that 76% of the patients still had detectable Neutralizing Antibodies (NAb) (1). Many studies reported short-term follow-up observations of less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others reported longitudinal observations, typically spanning less than 12 months post symptom onset (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Some studies reported contraction of anti-COVID humoral responses with a stronger initial decline (1,4,(23)(24)(25)27).…”
Section: Introductionmentioning
confidence: 63%
“…An important aspect of monitoring humoral responses has been having access to plasma from the same patients over 14 months. Most reports were based on cross-sectional analysis spanning less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) or up to 12 months (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Depending on the patient cohort, several studies reported a stronger initial contraction (1,4,(23)(24)(25)27) of anti-COVID humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in January 2021, the dominant VOC was Alpha (B.1.1.7), which remained the dominant VOC in the population until late June 2021 when Delta (B.1.617.2) became dominant and remained so for the duration of the study ( 1 ). Anti-N may wane faster than anti-S after an infection has subsided ( 35 , 36 ), thus the percentage of anti-N positivity underestimates cumulative infection ( 5 , 37 ). COVID-19-based deferrals (i.e., recent exposure/contact with an infected individual or symptomatic-based deferral) were rare (<0.1%) but more may have delayed donation, which could create a lag in measurement of anti-N infection rate.…”
Section: Discussionmentioning
confidence: 99%
“…It can be first conjectured that the priming effect of a prevaccination SARS-CoV-2 infection has progressively declined over time, being almost completely lost before receiving the vaccine booster dose, such that baseline SARS-CoV-2 seronegative and seropositive subjects would become a more homogenous population. This is not really surprising, since total anti-SARS-CoV-2 antibodies display a half-life between 50-110 days [20], with a seropositive rate decreasing to less than 36% after 12 months [21]. On the other hand, it is also conceivable that the administration of a BNT162b2 booster dose has provided such a strong stimulus to an already primed immunological memory (i.e., memory B cells) [22], such that another potent immunogenic trigger like an incident SARS-CoV-2 infection occurred after vaccine booster would be incapable to produce further significant increases of total anti-SARS-CoV-2 S antibodies levels over the threshold achieved with vaccine boosters.…”
Section: Discussionmentioning
confidence: 97%